1999
DOI: 10.1017/s1355838299981785
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal region of hPrp8 interacts with the conserved GU dinucleotide at the 5′ splice site

Abstract: A U5 snRNP protein, hPrp8, forms a UV-induced crosslink with the 59 splice site (59SS) RNA within splicing complex B assembled in trans-as well as in cis-splicing reactions. Both yeast and human Prp8 interact with the 59SS, branch site, polypyrimidine tract, and 39SS during splicing. To begin to define functional domains in Prp8 we have mapped the site of the 59SS crosslink within the hPrp8 protein. Immunoprecipitation analysis limited the site of crosslink to the C-terminal 50-60-kDa segment of hPrp8. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 34 publications
4
87
0
1
Order By: Relevance
“…The p220 that cross-linked to benzophenone at position −7 is most likely hPrp8p, as we and others have previously demonstrated that hPrp8p cross-links strongly near the end of the 5Ј exon and at the 5Ј splice site (Chiara et al 1996 and references therein; Reyes et al 1999;Le Hir et al 2000a). Likewise, the p170 that cross-linked only after exon ligation may well be SRm160-using a different antiserum from that used here (see Materials and Methods), we have previously shown that SRm160 can become cross-linked to benzophenone incorporated adjacent to the exon-exon junction of spliced mRNA (Le Hir et al 2000a).…”
Section: Enhanced 5ј Exon Association Of Ref/aly and Srp20 Upon Exon supporting
confidence: 51%
“…The p220 that cross-linked to benzophenone at position −7 is most likely hPrp8p, as we and others have previously demonstrated that hPrp8p cross-links strongly near the end of the 5Ј exon and at the 5Ј splice site (Chiara et al 1996 and references therein; Reyes et al 1999;Le Hir et al 2000a). Likewise, the p170 that cross-linked only after exon ligation may well be SRm160-using a different antiserum from that used here (see Materials and Methods), we have previously shown that SRm160 can become cross-linked to benzophenone incorporated adjacent to the exon-exon junction of spliced mRNA (Le Hir et al 2000a).…”
Section: Enhanced 5ј Exon Association Of Ref/aly and Srp20 Upon Exon supporting
confidence: 51%
“…2D). Furthermore, in HeLa extract, 5Ј ss has been observed to cross-link to a region close to residues 1,894-1,898 (corresponding to residues 1,966-1,970 in yPrp8) (32). Residues S1966, A1967, and S1970 (corresponding to Q1894, A1895, and K1898 in hPrp8) are indeed surface exposed in the ␤-finger domain structure, although two of the above residues are not conserved in yPrp8 (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The most likely candidate for an active-site protein in the spliceosome is Prp8. Prp8 has been cross-linked to the 5Ј splice site and appears to functionally interact with both splice sites during splicing (23,24). Recent crystallographic data show that a region of Prp8 that cross-links to the 5Ј splice site folds into an RNase H domain (25)(26)(27), which is remarkable, because RNase H domains catalyze the cleavage of phosphodiester bonds in RNA by using a 2-metal-ion mechanism (28).…”
mentioning
confidence: 99%